ETOS KERJA NELAYAN DALAM PERSPEKTIF MAQASHID SYARIAH: STUDI MASYARAKAT PESISIR - Masruroh, Nikmatul; Cahyani, Dyah Ayu; Ramadhani, Kurniawan; Fadli, Ahmad (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
ABSTRACT This research will discuss exploratively about coastal communities live which they have different habits from the other. For fulfill these different needs, there is a different work ethic between fishermen and other proffesions. The aims of this research are; first; provide an exploration of the work ethic of coastal communities, secondly; conducting of shariah maqashid analysis on the work ethic of fishermen in coastal communities. These two objectives are achieved using a qualitative approach using a case study type. The study was conducted in the coastal community of Pengambengan Jembrana District. Data was obtained by observation, interviews and collecting documentation. Data were analyzed using interpretive methods using the Miles and Huberman flow model. Data validity is carried out by triangulation sources and techniques so that data is obtained validly. This process producer results, firstly, the coastal communities work ethic was demonstrated by maximizing the use of time in meeting daily need, for example discipline, being punctual, work hardly, but this work ethic ignores the element of honesty, so that in work there is still cheating. Secondly, in the maqashid sharia analysis, the work ethic of coastal communities fufills the elements of kulliyatul khomsah, namely addin, annafs, al aql, annasl and al mal. Even though the addin’s honesty and hifd addin still need to be evaluated.